Innovative thrust vectoring system with moveable jet vanes integrated with a moveable diffuser – Measurement and analysis of selected nozzle performance parameters - Łukasz Krzysztof Nocoń; Marta Grzyb; Piotr Szmidt; Łukasz Marian Nowakowski (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2023)
The aim of the study described herein was to design, construct and test a demonstrator of a system to control the direction of the resultant thrust vector of a rocket motor to be used in short range anti-tank missiles with a mass of up to 15 kg. The novelty of the system is that the direction of the resultant thrust vector is manipulated by means of moveable jet vanes integrated with a moveable nozzle diffuser through telescopic connectors. The technology demonstrator was built using different materials and different manufacturing processes. The first versions were 3D printed from plastic materials. Minor modifications to the design were made at an early stage. The final version had the main components made of aluminum using CNC machining. The system, with and without jet vanes, was tested on a specially developed test rig equipped with a multi-axis sensor to measure forces and torques. The nozzle performance parameters measured and analyzed in this study were the components of the thrust vector, the moments and the effective vectoring angle. The findings show that the experimental data are in good agreement with the results of earlier simulations and that the demonstrator is fully operational.